2007
DOI: 10.1007/s10336-006-0105-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetically confirmed interbreeding between western Bonelli’s warbler (Phylloscopus bonelli) and wood warbler (P. sibilatrix)

Abstract: During May and June 2003, a mixed breeding pair consisting of a male western Bonelli's warbler (Phylloscopus bonelli) and a female wood warbler (P. sibilatrix) successfully raised six young in a broad-leafed forest near Jü nkerath, western Germany, an area far outside the regular breeding range of P. bonelli. The identity of the adult birds was confirmed by song, calls, colouration, and wing measurements. Based on blood samples taken from both parents and three juveniles, the potential interbreeding was analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To date, the few studies about this species focused on other topics (i.e. genetics, acoustics or migration/distribution range) rather than on the breeding biology itself (Helbig et al 1995, Bremond 1976, Prince et al 1997, Dietzen et al 2007, Pilastro et al 2008. In contrast to other European Phylloscopus species whose breeding biology has been well studied (e.g.…”
mentioning
confidence: 99%
“…To date, the few studies about this species focused on other topics (i.e. genetics, acoustics or migration/distribution range) rather than on the breeding biology itself (Helbig et al 1995, Bremond 1976, Prince et al 1997, Dietzen et al 2007, Pilastro et al 2008. In contrast to other European Phylloscopus species whose breeding biology has been well studied (e.g.…”
mentioning
confidence: 99%
“…Given that prior knowledge of the target sequences flanking the repeat regions is unnecessary, ISSR markers are simpler to employ than SSR methods (Zietkiewics et al 1994). This technique has been used for population genetic studies (Gupta et al 1994), the evaluation of genetic variability in plant breeding (McGregor et al 2000), the classification of species in plant systematics (Treutlein et al 2003), and the detection of hybridization in birds, reptiles and plants (Wolfe et al 1998, Wink et al 2001, Dietzen et al 2007). In birds, ISSR co-migrating bands have shown to be informative diagnostic characters in conjunction with nucleotide sequences in intraspecific and closely related species comparisons (e.g.…”
mentioning
confidence: 99%
“…Price and Bouvier (2002) concluded that complete loss of F1 fertility in birds generally takes millions of years. Hybridization has been proven once and suspected several times between the sympatric Wood Warbler Phylloscopus sibilatrix and Western Bonelli’s Warbler Phylloscopus bonelli (Dietzen et al. 2007 and references therein), which are genetically much more divergent (8.2–8.5%, uncorrected‐p; Helbig et al.…”
Section: Discussionmentioning
confidence: 99%